2017
DOI: 10.4025/actascianimsci.v39i3.34420
|View full text |Cite
|
Sign up to set email alerts
|

<b>Nutritional value of dual-purpose wheat genotypes pastures under grazing by dairy cows

Abstract: In the south of Brazil, one of the major limitations to milk production is the low forage availability during autumn and early winter. The use of dual-purpose wheat genotypes is one alternative to minimize the impact of low forage availability in addition to produce grains. Therefore, this study aimed to evaluate the nutritional value of two dual-purpose wheat genotypes (BRS Tarumã and BRS Umbu). Structural composition and forage nitrogen uptake were evaluated. The nutritional value of the forage was analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Meinerz et al (2011), evaluating wheat genotypes submitted to 3 cuts, observed average values between 24.2% (1 st cut), 22.8% (2 nd cut) and 15.6% (3 rd cut) crude protein. Quatrin et al (2017) observed values of 26.7, 27.8 and 27.6% crude protein for the 1 st , 2 nd and 3 rd cuts, respectively.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Meinerz et al (2011), evaluating wheat genotypes submitted to 3 cuts, observed average values between 24.2% (1 st cut), 22.8% (2 nd cut) and 15.6% (3 rd cut) crude protein. Quatrin et al (2017) observed values of 26.7, 27.8 and 27.6% crude protein for the 1 st , 2 nd and 3 rd cuts, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…According to the results of Meinerz et al (2012), wheat BRS Tarumã showed higher forage production in the second cut compared to the first one. Quatrin et al (2017), evaluating the nutritional value of dual-purpose wheat BRS Tarumã in 3 grazing cycles, observed higher forage yield in the last grazing cycle (2,070 kg ha -1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In these samples, it were determined the dry matter, crude protein and ether extract contents, according to Association of Official Agricultural Chemists (AOAC, 1995). The neutral and acid detergent fiber contents were determined by the method of Van Soest, Robertson, and Lewis (1991) and the estimation of the total digestible nutrients was obtained according to Quatrin et al (2017).…”
Section: Methodsmentioning
confidence: 99%
“…Dual-purpose winter cereals (Avena sativa L.; Avena strigosa Schreb; Hordeum vulgare L.; Secale cereale; Triticum aestivum; X Triticosecale Witt.) that allow the production of both pasture and grains during the same harvest cycle, have been used in several countries, including Australia (Sprague, Kirkegaard, Graham, Dove, & Kelman, 2014;Sprague et al, 2018), Brazil (Meinerz et 2012; Quatrin et al, 2017;Carvalho et al, 2018), China (Tian, Bell, Shen, & Wish, 2012;Hu et al, 2019), and Italy (Giunta, Motzo, Virdis, & Cabigliera, 2017;Giunta, Cadeddu, Mureddu, Virdis, & Motzo, 2020), among many others. They are seen as a way to intensify production on rural properties and increase profitability (Ates et al, 2018) by increasing integrated agricultural production systems in the short term (Henz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%